The Impact of a Water Resources Management RPG (Role-Playing Game) on the Players' Lives: An Analysis Based on Collective Subject Discourse - Mota, Fernanda P.; Born, Miriam B.; De Aguiar, Marilton S.; Adamatti, Diana F. (Proceedings - Frontiers in Education Conference, 2023)
This paper's main contribution is analyzing players' strategies and investigating the impact of gaming actions on players' lives. The games help understand a particular theme and allow the observation of the approach from a player's perspective. The sustainable management of water resources can be achieved when only the amount of water available locally is extracted from the available water resources. These resources are being recharged, naturally or artificially. Furthermore, we observe individuals related to the problem of water management and poor water management. As a result, we present the speeches through a semi-structured interview based on the Collective Subject Discourse (CSD) technique. The CSD consists of analyzing verbal material collected from the speeches (such as interviews or questionnaires), the ideas or central anchors, and the fundamental key expressions of these speeches. We compose the statements in the first person singular by the key expressions. Key Expressions (KE) are the most significant passages, and the Central Ideas (CI) synthesize the discursive content manifested in the KE. The case study presented in this work refers to the participatory negotiation of conflicts in the Lagoa Mirim and São Gonçalo Canal hydrographic basin, located in southern Brazil.